Cooperation and solidarity economy in heritage tourism with indigenous communities in Atacama - Muñoz Bascuñan, Alan (2021)
This work focuses on indigenous communities and tourist actors in the Atacama region, northern Chile, and try to propose a model to develop a tourist offer on the Inca Trail declared a World Heritage Site. The study is part of a regional project that sought to build an innovative offer with a characteristic stamp of the territory, and found as a problem that the indigenous communities present in the area had no links with the tourism sector, however they are the ones that frequent and protect the archaeological and patrimonial sites linked to the Inca trail. The results show that the articulation between tourism actors and indigenous communities allows the incorporation of new approaches and models for the construction of supply, as in this case based on cooperativism and solidarity economy, everyday aspects in these communities that inhabit the territories of the desert.